(untitled) (Medico Legal Update, 2020)
Adherence to ART is the primary determinant of viral suppression. Adherence of at least 95% is needed for optimal suppression. One of relationship with HAART is meaning in life. This study aimed at assessment meaning in life and adherence antiretroviral therapy before intervention about METART book. This method use descriptive statistic analysis to explain social demographic, meaning in life, and adherence antiretroviral therapy. The Result: Characteristics gender people new living with HIV/AIDS this study is 75,6% is Male with 38,5% homosexual. The age range of respondents is in the adult (65,4%). Single merital status is 74.4%. The total respondent with ARV medication is 30.8% under one year. 74.4% has meaningful life but 65,4% respondent has lack adherence ARV. Conclusion: This research get data pre intervention METART modul about demographic, meaning in life, and adherence ARV.